Mental health of students during the Covid-19 pandemic: The effects of different parental practices - Wu, Shin Ling *; Woo, Pei Jun *; Yap, Chin Choo *; Lim, Glen Johan Ri Young * (ACM Digital Library, 2022)
Mental health issues are a serious problem globally and have worsened since the Covid-19 pandemic. School students are experiencing high levels of stress due to the closure of schools. Students have to quickly adapt to online learning with minimal guidance during the early stage of the pandemic. Subsequently, students are allowed to go to school on a rotation basis. Therefore, a conducive home environment with support from parents plays an important role in helping students to cope with the uncertainties during the pandemic. We conducted a cross-sectional survey study where 761 high school students, aged between 13 to 18 years old were recruited in Malaysia. There was 468 female and 293 male students who participated in this study. Students’ mental health was measured using the Strengths and Difficulties Questionnaire (SDQ) while parental practices were measured using the Alabama Parenting Questionnaire. Parental practices were measured separately for father and mother in terms of positive parenting, involvement, poor monitoring and corporal punishment. Pearson correlation analysis showed that all parental practices were correlated significantly with mental health issues among high school students. However, based on the multiple regression analysis, only paternal poor monitoring, maternal corporal punishment, maternal positive parenting and paternal corporal punishment significantly predicted students’ mental health with paternal poor monitoring being the strongest predictor of students’ mental health. This study supported the importance of utilizing good parental practices in order to reduce mental health issues among students.